Response of LED lights intensity on lettuce production in a home vertical farm - Fuentes, Daniel; Flores, Jorge; Aguilar, Ariosto; Roblero, Rodrigo (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
On the market there are several LED lamps that were not designed to produce lettuce, however, they can be purchased at a low cost. In Mexico there is a lack of research on its use in small-scale vertical farms and hydroponic established in urban agriculture. The objective of this work was to measure the response of three commercial lamps with LED lights on the growth and morphogenesis of sangria lettuce grown in a low-cost home vertical farm. The sangria lettuce was subjected to three light intensities with different spectra and photoperiod after 30 days of growth the plant height, leaf length, leaf width, number of leaves and fresh weight were measured, and a one-way analysis of variance (ANOVA) and Duncan’s multiple comparison method was used through an algorithm designed in Python. According to the results, the highest fresh weight is made for a light intensity of 5700 lux. In the 2100 lux treatment, the highest height of the plant is performed and it was the treatment with the highest energy consumption. The production of lettuce at home is technically feasible, however, in addition to the light intensity, it is necessary to evaluate the quality (wavelengths) from the agronomic point of view.